Mycotoxins: The invisible enemy hidden in your food (Jóvenes en la Ciencia, 2026)
Mycotoxins are toxic compounds produced by fungi that may be present in everyday foods without altering their appearance, taste, or smell. In Mexico, due to climatic conditions and common storage practices, mycotoxins pose a constant risk in products such as corn, tortillas, coffee, nuts, milk, and pet food. This article blends narrative and scientific explanation to explore what mycotoxins are, how they affect human and animal health, where they are commonly found, and why they represent a silent danger. Practical recommendations are offered to help readers minimize exposure at home, accompanied by a reflection on the hidden impact of these compounds. The aim is to raise public awareness and promote a culture of food safety.